2014
DOI: 10.1002/14651858.cd003020.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Universal school-based prevention for illicit drug use

Abstract: Analysis 3.5. Comparison 3 Combined versus usual curricula, Outcome 5 Hard drug use < 12 months.. .. .. Analysis 3.6. Comparison 3 Combined versus usual curricula, Outcome 6 Hard drug use < 12 months.. .. .. Analysis 3.7. Comparison 3 Combined versus usual curricula, Outcome 7 Hard drug use ≥ 12 months.. .. .. Analysis 3.8. Comparison 3 Combined versus usual curricula, Outcome 8 Hard drug use ≥ 12 months.. .. .. Analysis 3.9. Comparison 3 Combined versus usual curricula, Outcome 9 Any drugs use < 12 months.. .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
147
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 216 publications
1
147
0
10
Order By: Relevance
“…The effectiveness of school-based drug prevention has been examined in a 2014 Cochrane systematic review. 18 In this review, 51 RCTs of universal (i.e. provided to all) school-based prevention interventions were identified, with only two studies from the UK.…”
Section: Evidence On the Effectiveness Of School-based Drug Preventionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effectiveness of school-based drug prevention has been examined in a 2014 Cochrane systematic review. 18 In this review, 51 RCTs of universal (i.e. provided to all) school-based prevention interventions were identified, with only two studies from the UK.…”
Section: Evidence On the Effectiveness Of School-based Drug Preventionmentioning
confidence: 99%
“…The authors noted that many studies did not describe the randomisation method or account for clustering (non-independence between children in the same school) in their analyses, despite all being cluster RCTs (cRCTs). 18 A second systematic review examined the effectiveness of peer-led interventions to prevent tobacco, alcohol or illicit drug use in 11-to 21-year-olds. 19 Pooled data from the three school-based RCTs reporting a drug use outcome (976 students, 38 schools) suggested that peer-led interventions had a small protective effect on cannabis use at ≥ 12 months.…”
Section: Evidence On the Effectiveness Of School-based Drug Preventionmentioning
confidence: 99%
See 3 more Smart Citations